Depth and Seasonal Effects on the Settlement Density of Two Mussel Species (Perna Perna and Mytilus Galloprovincialis) in Offshore, Agadir (Morocco) - Halla, Mohamed Id; Kassila, Jawad; Chattou, El Mustafa Ait; Ouaggajou, Yassine; El Aamri, Fatima; Benbani, Abdelbasset; Nhhala, Hassan (European Scientific Journal, ESJ, 2018)
A study of spat settlement of two mussel species was carried out in Agadir area on the North Atlantic Coast, between Jan 2002 and Jan 2003. The preferred depth of settlement and settlement period of both species were monitored on collectors suspended in offshore at three different depths (1, 5, 10 m). For Perna perna, the effect of season on settlement was consistent, with relatively higher settlement both in spring (286-462 spats.m-1 ) and in summer (406-594 spats.m-1 ). Similar abundances of settlers were found at 1 m and 5 m depth whatever the season, which suggests a homogeneous distribution of settlers of P. perna in the first 5 m of the sea water. For Mytilus galloprovincialis, the settlement was less patchy in time in regard to P. perna (Ï<0.05). Thus, the settlement was continuous from spring to autumn until 10 m depth. The filamentous structures (laces in polypropylene) used in this study are often designed to enhance the amount of settlers, however, the settlement densities of both species were very low. Consequently, the results suggest that larval supply has been the limiting factor in the settlement success, but not the lack of suitable substrates. Moreover, the study area has poor spat falls and seems to be not suitable for collection of mussel spat.